2007
DOI: 10.2337/db06-1552
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Uptake of Circulating Triglycerides in Nondiabetic Patients With Heart Disease

Abstract: Animal studies indicate that oversupply of fatty acids derived from the action of cardiac lipoprotein lipase (LPL) on plasma lipoproteins may contribute to myocardial dysfunction. However, the contribution of circulating triglycerides to myocardial fatty acid supply in humans is not known. Six postabsorptive nondiabetic subjects who were scheduled for diagnostic coronary angiography were studied. 14 C oleate and a lipid emulsion labeled with 3 H triolein were infused to assess myocardial uptake of free fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…With 55% survival in this series of patients with otherwise non-survivable cardiotoxic insult, ILE is likely to have facilitated survival for these patients. ILE is currently hypothesized to ameliorate drug cardiotoxicity by three mechanisms: provision of a "lipid sink" by providing a separate pharmacologic compartment into which the lipophilic drug may diffuse [6]; delivery of substrate to an energydepleted myocardium [7]; and improving function of select ion channels (e.g., calcium and sodium) present on the cell membrane in order to overcome myocardial conduction delays and poor inotropy [6]. Animal models of drug cardiotoxicity suggest that ILE administration may have superior survival efficacy over classic resuscitative therapies such as epinephrine [1,8] and vasopressin [1].…”
Section: Discussionmentioning
confidence: 99%
“…With 55% survival in this series of patients with otherwise non-survivable cardiotoxic insult, ILE is likely to have facilitated survival for these patients. ILE is currently hypothesized to ameliorate drug cardiotoxicity by three mechanisms: provision of a "lipid sink" by providing a separate pharmacologic compartment into which the lipophilic drug may diffuse [6]; delivery of substrate to an energydepleted myocardium [7]; and improving function of select ion channels (e.g., calcium and sodium) present on the cell membrane in order to overcome myocardial conduction delays and poor inotropy [6]. Animal models of drug cardiotoxicity suggest that ILE administration may have superior survival efficacy over classic resuscitative therapies such as epinephrine [1,8] and vasopressin [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally thought that the majority of FFAs are derived from the action of intracellular lipases on adipose tissue triglycerides, intravascular lipases such as lipoprotein lipase (LPL) can hydrolyze triglycerides in circulating triglyceride-rich lipoproteins and, thus, can be an additional source. It has previously been demonstrated that some fatty acids produced by intravascular lipolysis are released, or "spilled over," into the plasma FFA pool; this phenomenon has been documented in human adipose tissue, forearm tissue, and myocardium (7)(8)(9). A recent study (10) has shown high rates of spillover in the liver and in nonhepatic splanchnic tissues of fasting dogs.…”
mentioning
confidence: 99%
“…In this study the myocardium was only a minor contributor to total systemic TAG (VLDL) uptake (~3%) and systemic NEFA production (~0.5%) [2]. Previous studies had also suggested only limited VLDL-TAG utilisation by the human heart with about 10-20% of cardiac energy deriving from VLDL [31]), suggesting that in human heart, at least in the postabsorptive state, NEFAs may be more important cardiac substrates than VLDL-TAG [30,32].…”
Section: Cardiac Vldl-tag Utilisationmentioning
confidence: 84%
“…In the well-fed state it certainly represents the major transport form of endogenous TAG-FA, synthesised by de novo hepatic lipogenesis and exported to adipose tissue for storage; however, in the post-absorptive state it is assembled in the liver from adipose-derived NEFA, and it is unclear why NEFA cannot supply FA direct to oxidative tissues such as heart. Indeed, this pathway certainly occurs, but the issue of the A C C E P T E D M A N U S C R I P T Studies of cardiac A-V (coronary sinus) differences in non-diabetic patients undergoing cardiac catheterisation (usually in the post-absorptive state) found that some hearts extracted plasma (VLDL)TAG but not others (as previously noted [30]) whilst infused labelled TAG was consistently extracted (extraction fraction ~11%) [2]. TAGs and NEFAs accounted for ~17% and ~83%…”
Section: Cardiac Vldl-tag Utilisationmentioning
confidence: 99%
See 1 more Smart Citation